Characterization of red ginseng–drug interaction by CYP3A activity increased in high dose administration in mice. (17th July 2020) - Kim, Younah; Jo, Jung Jae; Cho, Piljoung; Shrestha, Riya; Kim, Kyu Min; Ki, Sung Hwan; Song, Kyung‐Sik; Liu, Kwang‐Hyeon; Song, Im‐Sook; Kim, Ju‐Hyun; Lee, Jae‐Mok; Lee, Sangkyu
Abstract: Ginseng ( Panax ginseng Meyer) is a popular traditional herbal medicine used worldwide. Patients often take ginseng preparations with other medicines where the ginseng dose could exceed the recommended dose during long‐term administration. However, ginseng–drug interactions at high doses of ginseng are poorly understood. This study showed the possibility of herb–drug interactions between the Korean red ginseng (KRG) extract and cytochrome P450 (CYP) substrates in higher administration in mice. The CYP activities were determined in vivo after oral administration of KRG extract doses of 0.5, 1.0, and 2.0 g/kg for 2 or 4 weeks by monitoring the concentration of five CYP substrates/metabolites in the blood. The area under the curve for OH‐midazolam/midazolam catalysed by CYP3A was increased significantly by the administration of 2.0 g/kg KRG extract for 2 and 4 weeks. CYP3A‐catalysed midazolam 1ʹ‐hydroxylation also increased significantly in a dose‐ and time‐dependent manner in the S9 fraction of mouse liver which was not related to induction by transcription. Whereas CYP2D‐catalysed dextromethorphan O ‐deethylation decreased in a dose‐ and time‐dependent manner in vivo. In conclusion, interactions were observed between KRG extract and CYP2D and CYP3A substrates at subchronic–high doses of KRG administration in mice.